Ankle injury rehabilitation (AIR): a feasibility randomised controlled trial comparing functional bracing to plaster cast in the treatment of adult ankle fractures - Rebecca S. Kearney; Rebecca McKeown; Daniel Gallacher; Jaclyn Brown; Dipesh Mistry; Nick Parsons; Jonathan Young; Matthew Costa (Pilot and Feasibility Studies, 2019)
Abstract Background Approximately 9% of a trauma surgeon’s workload in the UK is managing ankle fractures. Following an ankle fracture immobilisation with a plaster cast or removable orthotic is usual. The aim of this research was to assess the feasibility of a large multi-centre randomised controlled trial (RCT) to evaluate the difference between plaster cast and a removable orthotic for the management of adults with an ankle fracture. Methods A feasibility randomised controlled trial was undertaken in a UK trauma hospital in adults with an ankle fracture for which the treating clinician would consider plaster cast a reasonable management option. Exclusions included open or pathological fracture, unable to adhere to trial procedures, had other lower limb injury or required close contact casting. Participants were randomised using an independent telephone service to receive either plaster cast or removable orthotic. The primary outcome was to determine the recruitment and follow-up rates at 6 weeks, 3 and 6 months to assess the feasibility of a full RCT. Results Eighty five eligible patients presented during the 10-month recruitment period, 50 consented. Two patients were randomised who did not fulfil the eligibility criteria (protocol deviations), and 1 patient from each group crossed over. Follow-up at each time point was 92% at 6 weeks; 74% at 3 months and 83% at 6 months. Conclusions Recruitment and follow-up data demonstrated feasibility of conducting a larger-scale randomised controlled trial. The distributional properties of the patient-reported outcome measures will be used to determine future sample sizes. Trial registrations This study is registered with the ISRCTN (ISRCTN17809322), assigned 5 November 2015 and approved by the NRES Committee (The Black Country, 15/WM/0340), protocol version 2.0 (17 November 2015). It is co-sponsored by the University Hospitals Coventry and Warwickshire NHS Trust and University of Warwick and funded by the NIHR Research for Patient Benefit (PB-PG-0614-34,009). The trial sponsors have no direct involvement in any aspects of study design, conduct or decision to submit the report for publication.